Factor Related to Musculoskeletal Disorders among Durian Farmers in Kanchanadit District, Surat Thani Province - Chokprasit, Parnchon; Puangpee, Jirattikarn; Khotpan, Thanyarat; Khongkan, Nantawan; Thaikert, Ratchadaporn; Mala, jirawat (Health Science Journal of Thailand, 2024)
In a cross-sectional analytical study, the aim was to identify risk factors and evaluate ergonomic risks associated with working postures leading to musculoskeletal disorders among 199 durian farmers in Kanchanadit District, Surat Thani Province. Data was gathered through questionnaires and the REBA (Rapid Entire Body Assessment) risk assessment form. Statistical analysis involved descriptive statistics and multiple logistic regression. The study revealed that the majority of durian farmers worked 5-7 days a week, without breaks for 1-4 hours per day (54.27%). All farmers repeated the same postures and used tools such as water buckets, knives, and sickles, 82.41% using heavy tools. The prevalence of musculoskeletal injuries, within the past 12 months and 7 days, was highest in the lower back area (63.82% and 71.36%, respectively). The REBA assessment indicated that 61.31% of farmers were at level 4 risk. Additionally, risk factors associated with low back pain included working without consecutive breaks for 5-8 hours per day (adjusted odds ratio (AOR =3.45, 95%CI: 1.52-7.80). Conversely, protective factors for low back pain included farmers aged over 50 years (AOR = 0.32, 95% CI: 0.10-0.95) and physical activity (AOR = 0.44, 95% CI: 0.20-0.92). These findings suggest that durian farmers are at high risk and highlight the urgent need to improve their working postures to prevent musculoskeletal issues. m.